Transmission potential of paromomycin-resistant Leishmania infantum and Leishmania donovani. (30th December 2019) - Hendrickx, S; Van Bockstal, L; Aslan, H; Sadlova, J; Maes, L; Volf, P; Caljon, G
Abstract: Objectives: Former studies demonstrated quick selection of paromomycin resistance for Leishmania infantum and Leishmania donovani accompanied by increased fitness. The present study aimed to interpret these findings in an epidemiological context by comparing infection of WT and experimentally derived paromomycin-resistant strains in the sand fly vector. Methods: Depending on the Leishmania species, Lutzomyia longipalpis and Phlebotomus perniciosus or Phlebotomus argentipes sand flies were artificially infected with procyclic promastigotes of WT and paromomycin-resistant L. infantum (MHOM/FR/96/LEM3323-cl4) or L. donovani (MHOM/NP/03/BPK275/0-cl18). The infection rate and gut/stomodeal valve colonization were determined to monitor parasite phenotypic behaviour within the vector. The impact of the previously described gain of fitness in the vertebrate host on infectivity for the vector was assessed by feeding L. longipalpis on Syrian golden hamsters heavily infected with either WT or paromomycin-resistant parasites. Results: WT and paromomycin-resistant Leishmania of both species behaved similarly in terms of infection and parasite location within the studied sand fly species. Blood feeding on infected hamsters did not reveal differences in acquisition of WT and paromomycin-resistant parasites, despite the higher organ burdens observed for the paromomycin-resistant strain. Strains remained resistant after passage in the vector. Conclusions: Although paromomycin-resistant parasites show an increased parasite fitness in vitro and in laboratory rodents, the intrinsic infection potential of paromomycin-resistant parasites remains unaltered in the sand fly. Of importance is the fact that paromomycin-resistant Leishmania are able to complete development in the natural vectors and produce stomodeal infection with metacyclic forms, which clearly suggests their potential to spread and circulate in nature.